Travel Training for Older Adults Part I: A Handbook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Report 168: Travel Training for Older Adults, Part I: A Handbook presents a comprehensive roadmap for designing a travel training program to meet the mobility needs of older persons. The Handbook, Part I, addresses the primary components of an effective travel training program and provides an extensive set of guidelines for transit agencies and human services providers on how to build and implement training programs to help older adults who are able to use fixed-route public transit.The supplemental research report, Part II, reviews the research plan that produced this report as well as the case studies used to formulate the overall strategic program.An Executive Summary brochure summarizes the highlights of TCRP Report 168, Parts I and II.
Keywords: Transportation and Infrastructure

Travel Training for Older Adults Part II: Research Report and Case Studies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Report 168: Travel Training for Older Adults Travel Training for Older Adults, Part II: Research Report and Case Studies presents a comprehensive roadmap for designing a travel training program to meet the mobility needs of older persons. This supplemental research report reviews the research plan that produced this report as well as the case studies used to formulate the overall strategic program.The Handbook, Part I, addresses the primary components of an effective travel training program to meet the mobility needs of older persons. It provides an extensive set of guidelines for transit agencies and human services providers on how to build and implement training programs to help older adults who are able to use fixed-route public transit.An Executive Summary brochure summarizes the highlights of TCRP Report 168, Parts I and II.
Keywords: Transportation and Infrastructure

Financing Long-Term Services and Supports for Individuals with Disabilities and Older Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Financing Long-Term Services and Supports for Individuals with Disabilities and Older Adults is the summary of a workshop convened in June 2013 by the Forum on Aging, Disability, and Independence of the Institute of Medicine and the National Research Council to examine the financing of long-term services and supports for working-age individuals with disabilities and among individuals who are developing disabilities as they age. The workshop covered both older adults who acquire disabilities and younger adults with disabilities who may acquire additional impairments as they age, the target population of the Forum's work. The challenges associated with financing long-term services and supports for people with disabilities impacts all age groups. While there are important differences between the characteristics of programs developed for different age groups, and specific populations may have different needs, this workshop addressed the financing sources for long-term services and supports in general, noting specific differences as appropriate. The financing of long-term services and supports has become a major issue in the United States. These are the services and supports that individuals with disabilities, chronic conditions, and functional impairments need in order to live independently, such as assistance with eating, bathing, and dressing. Long-term services and supports do not include the medical or nursing services required to manage health conditions that may be responsible for a disabling condition. At least 11 million adults ages 18 and over receive long-term services and supports. Only a little more than half of them - 57 percent - are ages 65 or older. One study found that about 6 percent of people turning 65 in 2005 could expect to have expenses of more than $100,000 for long-term services and supports. Financing Long-Term Services and Supports for Individuals with Disabilities and Older Adults discusses the scope and trends of current sources of financing for long-term services and supports for working-age individuals with disabilities and older adults aging into disability, including income supports and personal savings. This report considers the role of families, business, and government in financing long-term services and supports and discusses implications of and opportunities for current and innovative approaches.
Keywords: Health and Medicine

Undergraduate Chemistry Education: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Undergraduate Chemistry Education is the summary of a workshop convened in May 2013 by the Chemical Science Roundtable of the National Research Council to explore the current state of undergraduate chemistry education. Research and innovation in undergraduate chemistry education has been done for many years, and one goal of this workshop was to assist in the transfer of lessons learned from the education research community to faculty members whose expertise lies in the field of chemistry rather than in education. Through formal presentations and panel discussions, participants from academia, industry, and funding organizations explored drivers of change in science, technology, engineering and mathematics education; innovations in chemistry education; and challenges and opportunities in chemistry education reform. Undergraduate Chemistry Education discusses large-scale innovations that are transferable, widely applicable, and/or proven successful, with specific consideration of drivers and metrics of change, barriers to implementation of changes, and examples of innovation in the classroom.
Keywords: Math, Chemistry, and Physics; Education

STEM Integration in K-12 Education: Status, Prospects, and an Agenda for Research - National Academy of Engineering; National Research Council (The National Academies Press, 2014)
STEM Integration in K-12 Education examines current efforts to connect the STEM disciplines in K-12 education. This report identifies and characterizes existing approaches to integrated STEM education, both in formal and after- and out-of-school settings. The report reviews the evidence for the impact of integrated approaches on various student outcomes, and it proposes a set of priority research questions to advance the understanding of integrated STEM education. STEM Integration in K-12 Education proposes a framework to provide a common perspective and vocabulary for researchers, practitioners, and others to identify, discuss, and investigate specific integrated STEM initiatives within the K-12 education system of the United States. STEM Integration in K-12 Education makes recommendations for designers of integrated STEM experiences, assessment developers, and researchers to design and document effective integrated STEM education. This report will help to further their work and improve the chances that some forms of integrated STEM education will make a positive difference in student learning and interest and other valued outcomes.
Keywords: Education; Engineering and Technology

Assessing Health Professional Education: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Assessing Health Professional Education is the summary of a workshop hosted by the Institute of Medicine's Global Forum on Innovation in Health Professional Education to explore assessment of health professional education. At the event, Forum members shared personal experiences and learned from patients, students, educators, and practicing health care and prevention professionals about the role each could play in assessing the knowledge, skills, and attitudes of all learners and educators across the education to practice continuum. The workshop focused on assessing both individuals as well as team performance. This report discusses assessment challenges and opportunities for interprofessional education, team-based care, and other forms of health professional collaborations that emphasize the health and social needs of communities.
Keywords: Education; Health and Medicine

Graduate Medical Education That Meets the Nation's Health Needs - Institute of Medicine (The National Academies Press, 2014)
Today's physician education system produces trained doctors with strong scientific underpinnings in biological and physical sciences as well as supervised practical experience in delivering care. Significant financial public support underlies the graduate-level training of the nation's physicians. Two federal programs—Medicare and Medicaid—distribute billions each year to support teaching hospitals and other training sites that provide graduate medical education. Graduate Medical Education That Meets the Nation's Health Needs is an independent review of the goals, governance, and financing of the graduate medical education system. This report focuses on the extent to which the current system supports or creates barriers to producing a physician workforce ready to provide high-quality, patient-centered, and affordable health care and identifies opportunities to maximize the leverage of federal funding toward these goals. Graduate Medical Education examines the residency pipeline, geographic distribution of generalist and specialist clinicians, types of training sites, and roles of teaching and academic health centers. The recommendations of Graduate Medical Education will contribute to the production of a better prepared physician workforce, innovative graduate medical education programs, transparency and accountability in programs, and stronger planning and oversight of the use of public funds to support training. Teaching hospitals, funders, policy makers, institutions, and health care organizations will use this report as a resource to assess and improve the graduate medical education system in the United States.
Keywords: Health and Medicine; Education

Surmounting the Barriers: Ethnic Diversity in Engineering Education: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Surmounting the Barriers: Ethnic Diversity in Engineering Education is the summary of a workshop held in September 2013 to take a fresh look at the impediments to greater diversification in engineering education. The workshop brought together educators in engineering from two- and four-year colleges and staff members from the three sponsoring organizations: the National Science Foundation, the National Academy of Engineering and the American Society for Engineering Education. While the goal of diversifying engineering education has long been recognized, studied, and subjected to attempted interventions, progress has been fitful and slow. This report discusses reasons why past recommendations to improve diversity had not been adopted in full or in part. Surmounting the Barriers identifies a series of key impediments, including a lack of incentives for faculty and institutions; inadequate or only short-term financial support; an unsupportive institutional and faculty culture and environment; a lack of institutional and constituent engagement; and inadequate assessments, metrics, and data tracking. The report also shares success stories about instances where barriers to diversity have been identified and surmounted, and the resources that could enable real solutions to implement steps toward progress.
Keywords: Engineering and Technology; Education

Climate Change Education: Preparing Future and Current Business Leaders: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Climate change poses challenges as well as opportunities for businesses and, broadly speaking for the entire economy. Businesses will be challenged to provide services or products with less harmful influence on the climate; respond to a changing policy, regulatory, and market environment; and provide new services and products to help address the challenges of a changing climate. Many businesses are beginning to see climate change as another context within which they need to consider their core functions of strategy, finance, operations, marketing, and their regulatory environments, a context that poses both risks and opportunities. Climate Change Education: Preparing Current and Future Business Leaders is the summary of a workshop hosted by the National Research Council's Board on Science Education in March 2013 to explore issues associated with teaching climate change-related topics in business schools. The workshop focused on major gaps in understanding of climate and sustainability education in postsecondary professional schools of business. The workshop also connected the topic of climate education for current and future business leaders with a broader discussion on climate change education and how they influence and can benefit each other. This report discusses the role that business schools could play in preparing future corporate leaders for the challenges and opportunities that climate change poses.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

Airport Escalators and Moving Walkways—Cost-Savings and Energy Reduction Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Report 117: Airport Escalators and Moving Walkways—Cost-Savings and Energy Reduction Technologies provides a systematic approach to identifying, evaluating, and selecting cost-saving and energy reduction technologies for airport escalators and moving walkways. A spreadsheet tool that supplements the report is bound in the hardcopy of the report as CRP-CD-156.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Climate Change Education: Engaging Family Private Forest Owners on Issues Related to Climate Change: A Workshop Summary - National Research Council (The National Academies Press, 2014)
The forested land in the United States is an asset that is owned and managed not only by federal, state, and local governments, but also by families and other private groups, including timber investment management organizations and real estate investment trusts. The more than 10 million family forestland owners manage the largest percentage of forestland acreage (35 percent) and the majority of the privately owned forestland (62 percent). The Forest Service of the United States Department of Agriculture, which is responsible for the stewardship of all of the nation's forests, has long worked with private owners of forestland on forest management and preservation. At a time when all forestland is facing intensified threats because of the long-term effects of global climate change, the Forest Service recognizes that family forestland owners play a key role in protecting forestland. It is working to identify optimal ways to engage this diverse group and support them in mitigating threats to the biologically diverse land they own or manage. Climate Change Education: Engaging Family Private Forest Owners on Issues Related to Climate Change is the summary of a workshop, convened by the National Research Council's Board on Science Education and Board on Environmental Change and Society as part of its Climate Change Education Roundtable series, to explore approaches to the challenges that face state foresters, extension agents, private forestry consultants, and others involved with private family forestland owners on how to take climate change into consideration when making decisions about their forests. The workshop focused on how findings from the behavioral, social, and educational sciences can be used to help prepare for the impacts of climate change. The workshop participants discussed the threats to forests posed by climate change and human actions; private forestland owners' values, knowledge, and dispositions about forest management, climate change, and related threats; and strategies for improving communication between forestland owners and service providers about forest management in the face of climate change.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

The Climate Change Educational Partnership: Climate Change, Engineered Systems, and Society: A Report of Three Workshops - National Academy of Engineering (The National Academies Press, 2014)
Societies develop engineered systems to address or mediate climate-related problems, such as drought, sea-level rise or wildfire control; the mediation involves public trust, public engagement, and governance. In these efforts, societies also decide - intentionally or implicitly - questions of justice and sustainability, such as what areas will receive mediation measures, what types of measures will be used, and what levels and kinds of local impacts are tolerated. In September 2010, the Center for Engineering, Ethics, and Society at the National Academy of Engineering began working with four other partners on a Climate Change Educational Partnership Phase I planning grant from the National Science Foundation. The project focused on defining and characterizing the societal and pedagogical challenges posed by the interactions of climate change, engineered systems and society, and identifying the educational efforts that a network could use to enable engineers, teachers, students, policymakers, and the public to meet the challenges. The project also aimed to build awareness of the complexities among a diverse set of communities affected by climate change and engineered systems and to engage the communities in addressing these challenges. The Climate Change Educational Partnership is the summary of three workshops convened over the course of the grant on the interactions of climate change with engineered systems in society and the educational efforts needed to address them. The first workshop provided the partners with an introduction to the varied social and technical dimensions found in the relationships among climate, engineered systems, and society. The second workshop built on the common language developed in the first. It allowed the partners to expand involvement in the project to include representatives from community and tribal colleges, professional societies and business. It examined the opportunities and challenges for formal and informal education, particularly in engineering classrooms and science museums, to prepare students and citizens to address these issues. The third workshop allowed the partners to broaden further the discussion and the audience. It solicited participation from government officials, Native American tribal representatives, professional society leaders, as well as educators, artists, scientists, and engineers who are developing programs that can manage change and educate students and citizens in ways that foster their leadership skills. The Climate Change Educational Partnership will be a useful resource to engineers, educators, corporate leaders, local and regional officials, members of professional societies, and others in their efforts to understand and address the challenges of climate change and its societal impacts.
Keywords: Engineering and Technology

Hearing Loss and Healthy Aging: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Being able to communicate is a cornerstone of healthy aging. People need to make themselves understood and to understand others to remain cognitively and socially engaged with families, friends, and other individuals. When they are unable to communicate, people with hearing impairments can become socially isolated, and social isolation can be an important driver of morbidity and mortality in older adults. Despite the critical importance of communication, many older adults have hearing loss that interferes with their social interactions and enjoyment of life. People may turn up the volume on their televisions or stereos, miss words in a conversation, go to fewer public places where it is difficult to hear, or worry about missing an alarm or notification. In other cases, hearing loss is much more severe, and people may retreat into a hard-to-reach shell. Yet fewer than one in seven older Americans with hearing loss use hearing aids, despite rapidly advancing technologies and innovative approaches to hearing health care. In addition, there may not be an adequate number of professionals trained to address the growing need for hearing health care for older adults. Further, Medicare does not cover routine hearing exams, hearing aids, or exams for fitting hearing aids, which can be prohibitively expensive for many older adults. Hearing Loss and Healthy Aging is the summary of a workshop convened by the Forum on Aging, Disability, and Independence in January 2014 on age-related hearing loss. Researchers, advocates, policy makers, entrepreneurs, regulators, and others discussed this pressing social and public health issue. This report examines the ways in which age-related hearing loss affects healthy aging, and how the spectrum of public and private stakeholders can work together to address hearing loss in older adults as a public health issue.
Keywords: Health and Medicine

The Growth of Incarceration in the United States: Exploring Causes and Consequences - National Research Council (The National Academies Press, 2014)
After decades of stability from the 1920s to the early 1970s, the rate of imprisonment in the United States more than quadrupled during the last four decades. The U.S. penal population of 2.2 million adults is by far the largest in the world. Just under one-quarter of the world's prisoners are held in American prisons. The U.S. rate of incarceration, with nearly 1 out of every 100 adults in prison or jail, is 5 to 10 times higher than the rates in Western Europe and other democracies. The U.S. prison population is largely drawn from the most disadvantaged part of the nation's population: mostly men under age 40, disproportionately minority, and poorly educated. Prisoners often carry additional deficits of drug and alcohol addictions, mental and physical illnesses, and lack of work preparation or experience. The growth of incarceration in the United States during four decades has prompted numerous critiques and a growing body of scientific knowledge about what prompted the rise and what its consequences have been for the people imprisoned, their families and communities, and for U.S. society. The Growth of Incarceration in the United States examines research and analysis of the dramatic rise of incarceration rates and its affects. This study makes the case that the United States has gone far past the point where the numbers of people in prison can be justified by social benefits and has reached a level where these high rates of incarceration themselves constitute a source of injustice and social harm. The Growth of Incarceration in the United States recommends changes in sentencing policy, prison policy, and social policy to reduce the nation's reliance on incarceration. The report also identifies important research questions that must be answered to provide a firmer basis for policy. The study assesses the evidence and its implications for public policy to inform an extensive and thoughtful public debate about and reconsideration of policies.
Keywords: Behavioral and Social Sciences

New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves—they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains—including those in child welfare, economic support, criminal justice, education, and health care systems—and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.
Keywords: Behavioral and Social Sciences; Health and Medicine

Caffeine in Food and Dietary Supplements: Examining Safety: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Caffeine in Food and Dietary Supplements is the summary of a workshop convened by the Institute of Medicine in August 2013 to review the available science on safe levels of caffeine consumption in foods, beverages, and dietary supplements and to identify data gaps. Scientists with expertise in food safety, nutrition, pharmacology, psychology, toxicology, and related disciplines; medical professionals with pediatric and adult patient experience in cardiology, neurology, and psychiatry; public health professionals; food industry representatives; regulatory experts; and consumer advocates discussed the safety of caffeine in food and dietary supplements, including, but not limited to, caffeinated beverage products, and identified data gaps. Caffeine, a central nervous stimulant, is arguably the most frequently ingested pharmacologically active substance in the world. Occurring naturally in more than 60 plants, including coffee beans, tea leaves, cola nuts and cocoa pods, caffeine has been part of innumerable cultures for centuries. But the caffeine-in-food landscape is changing. There are an array of new caffeine-containing energy products, from waffles to sunflower seeds, jelly beans to syrup, even bottled water, entering the marketplace. Years of scientific research have shown that moderate consumption by healthy adults of products containing naturally-occurring caffeine is not associated with adverse health effects. The changing caffeine landscape raises concerns about safety and whether any of these new products might be targeting populations not normally associated with caffeine consumption, namely children and adolescents, and whether caffeine poses a greater health risk to those populations than it does for healthy adults. This report delineates vulnerable populations who may be at risk from caffeine exposure; describes caffeine exposure and risk of cardiovascular and other health effects on vulnerable populations, including additive effects with other ingredients and effects related to pre-existing conditions; explores safe caffeine exposure levels for general and vulnerable populations; and identifies data gaps on caffeine stimulant effects.
Keywords: Food and Nutrition

The Evidence for Violence Prevention Across the Lifespan and Around the World: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
The Evidence for Violence Prevention Across the Lifespan and Around the World is the summary of a workshop convened in January 2013 by the Institute of Medicine's Forum on Global Violence Prevention to explore value and application of the evidence for violence prevention across the lifespan and around the world. As part of the Forum's mandate is to engage in multisectoral, multidirectional dialogue that explores crosscutting approaches to violence prevention, this workshop examined how existing evidence for violence prevention can continue to be expanded, disseminated, and implemented in ways that further the ultimate aims of improved individual well-being and safer communities. This report examines violence prevention interventions that have been proven to reduce different types of violence (e.g., child and elder abuse, intimate partner and sexual violence, youth and collective violence, and self-directed violence), identifies the common approaches most lacking in evidentiary support, and discusses ways that proven effective interventions can be integrated or otherwise linked with other prevention programs.
Keywords: Health and Medicine

STEM Learning Is Everywhere: Summary of a Convocation on Building Learning Systems - National Research Council (The National Academies Press, 2014)
Science, technology, engineering, and mathematics (STEM) permeate the modern world. The jobs people do, the foods they eat, the vehicles in which they travel, the information they receive, the medicines they take, and many other facets of modern life are constantly changing as STEM knowledge steadily accumulates. Yet STEM education in the United States, despite the importance of these subjects, is consistently falling short. Many students are not graduating from high school with the knowledge and capacities they will need to pursue STEM careers or understand STEM-related issues in the workforce or in their roles as citizens. For decades, efforts to improve STEM education have focused largely on the formal education system. Learning standards for STEM subjects have been developed, teachers have participated in STEM-related professional development, and assessments of various kinds have sought to measure STEM learning. But students do not learn about STEM subjects just in school. Much STEM learning occurs out of school—in organized activities such as afterschool and summer programs, in institutions such as museums and zoos, from the things students watch or read on television and online, and during interactions with peers, parents, mentors, and role models. To explore how connections among the formal education system, afterschool programs, and the informal education sector could improve STEM learning, a committee of experts from these communities and under the auspices of the Teacher Advisory Council of the National Research Council, in association with the California Teacher Advisory Council organized a convocation that was held in February 2014. Entitled "STEM Learning Is Everywhere: Engaging Schools and Empowering Teachers to Integrate Formal, Informal, and Afterschool Education to Enhance Teaching and Learning in Grades K-8," the convocation brought together more than 100 representatives of all three sectors, along with researchers, policy makers, advocates, and others, to explore a topic that could have far-reaching implications for how students learn about STEM subjects and how educational activities are organized and interact. This report is the summary of that meeting. STEM Learning is Everywhere explores how engaging representatives from the formal, afterschool, and informal education sectors in California and from across the United States could foster more seamless learning of STEM subjects for students in the elementary and middle grades. The report also discusses opportunities for STEM that may result from the new expectations of the Next Generation Science Standards and the Common Core Standards for Mathematics and Language Arts.
Keywords: Education

Preventing Psychological Disorders in Service Members and Their Families: An Assessment of Programs - Institute of Medicine (The National Academies Press, 2014)
Being deployed to a war zone can result in numerous adverse psychological health conditions. It is well documented in the literature that there are high rates of psychological disorders among military personnel serving in Operation Enduring Freedom in Afghanistan and Operation Iraqi Freedom in Iraq as well as among the service members' families. For service members' families, the degree of hardship and negative consequences rises with the amount of the service members' exposure to traumatic or life-altering experiences. Adult and child members of the families of service members who experience wartime deployments have been found to be at increased risk for symptoms of psychological disorders and to be more likely to use mental health services. In an effort to provide early recognition and early intervention that meet the psychological health needs of service members and their families, DOD currently screens for many of these conditions at numerous points during the military life cycle, and it is implementing structural interventions that support the improved integration of military line personnel, non-medical caregivers, and clinicians, such as RESPECT-Mil (Re-engineering Systems of Primary Care Treatment in the Military), embedded mental health providers, and the Patient-Centered Medical Home. Preventing Psychological Disorders in Service Members and Their Families evaluates risk and protective factors in military and family populations and suggests that prevention strategies are needed at multiple levels - individual, interpersonal, institutional, community, and societal - in order to address the influence that these factors have on psychological health. This report reviews and critiques reintegration programs and prevention strategies for PTSD, depression, recovery support, and prevention of substance abuse, suicide, and interpersonal violence.
Keywords: Health and Medicine

Next Generation Science Standards Resource Value Pack (The National Academies Press, 2014)
Get the resources you need to understand, implement, and evaluate the teaching of the Next Generation Science Standards. These titles will be an essential resource for teachers, science department leaders, science coaches, education administration, and curriculum developers. Along with the print edition of the Next Generation Science Standards: For States, By States, this bundle comes with: A Framework for K-12 Science Education, the NRC report that formed the basis for the NGSS Developing Assessments for the Next Generation Science Standards, a report that offers strategies for how states and school districts might assess student proficiency with the new standards Buy all three books together to save on the total list price!
Keywords: Education